Morphological classification of digestive neuroendocrine neoplasms: the current concepts and controversies - V. V. Delektorskaya (Успехи молекулярной онкологии, 2016)
Neuroendocrine tumors comprise the heterogeneous group of malignant epithelial neoplasms, the diagnosis of which is based on their histopathologic features and immunohistochemical profile. For neuroendocrine tumors of the digestive system in the World Health Organization (2010) classification were introduced main categories, the nomenclature, criterions for grading and staging. However, accumulating evidence demonstrates actual controversies in the histopathology of neuroendocrine neoplasms and unreserved problems in their classification. In this review we focus on some of the common features of neuroendocrine neoplasms, their classification, and differences in pathology, biology of the main categories, and the most important immunohistochemical markers.